(untitled) (Journal of the College of Basic Education, 2020)
This research focuses attention on the audience of horror films, and discuss the nature of the relationship between them and recipients by highlighting the effects of their exposure to the type of horror type of horror and reflection in the behavior of individuals to varying degrees, exposed as highly suitable for the most important theories that intensified to study the psychological and behavioral effects in people exposed film. The study also answers many questions that have raised urgent answers related to the ecological and psychological level associated with the motivation behind the practice of exposures in viewers of this type of horror. At this point, it is a natural reason for the urgent need to know that this generation has spent a long time standing at the box office to get a ticket for the increase in horror movies, especially in the third millennium. Hence comes the source of concern represented by the existence of a large area of culture which dominate contemporary societies, and must for this phenomenon include tendencies deviant produces a different culture, then the horror will not be an individual feeling, but it turns into a transformation that seeks to reformulate the collective consciousness, to become the vast majority of the recipients kidnapped on board the taste of terror film